2017
DOI: 10.1002/ijc.30674
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic gene changes determine the successful establishment of stable renal cancer cell lines from tumor tissue

Abstract: Human tumor cell lines, especially those with complete data and follow-up, are important tools in tumor biological studies. Clear cell renal cell cancer (ccRCC) is not sensitive to radiotherapy or chemotherapy, and treatment of patients with distant metastasis relies on targeted therapy. Here, we report the establishment of seven new ccRCC stable cell lines that were continuously cultured for more than 20 generations among 81 cases of renal cell cancer. Moreover, gene expression and methylation in the establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Furthermore, CYSLTR2 , cysteinyl leukotriene receptor 2, has been related to uveal melanoma progression . The upregulation of SULT1C4 would seem fundamental in maintaining establishment primary renal cell lines ccRCC . GIF , gastric intrinsic factor gene encodes a glycoprotein secreted by parietal cells of the gastric mucosa and is required for adequate absorption of vitamin B12.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CYSLTR2 , cysteinyl leukotriene receptor 2, has been related to uveal melanoma progression . The upregulation of SULT1C4 would seem fundamental in maintaining establishment primary renal cell lines ccRCC . GIF , gastric intrinsic factor gene encodes a glycoprotein secreted by parietal cells of the gastric mucosa and is required for adequate absorption of vitamin B12.…”
Section: Discussionmentioning
confidence: 99%
“…gov/ geo/, GSE82221, GSE89649). [17][18][19][20] Methylation analysis of the UHB cohort was performed using bisulfite-specific quantitative real-time PCR employing methylation-unspecific primers and probe pairs specifically and competitively binding methylated and unmethylated template DNA, respectively. This quantitative methylation-specific PCR (qMSP) is described in detail by Lehmann and Kreipe.…”
Section: Methylation Analysismentioning
confidence: 99%
“…FAM196B is a protein coding gene and locates at 5q35.1. At present, it was only found that FAM196B was up-regulated in renal carcinoma 13 .DNA methylation of FAM196B showed high differences in breast cancer 18 .Recent studies showed that FAM196B expression was up-regulated in gastric cancer (GC) tissues and associated with poor tumor histology and T stage of GC. FAM196B also could promote gastric cancer cell proliferation through activating AKT signaling pathway 19 .…”
Section: Discussionmentioning
confidence: 98%
“…Chen and colleagues reported that FAM196B expressed higher in the embryonic ovary than the testis during mouse gonad development 12 . More recently, it was also reported that FAM196B was up-regulated in clear cell renal cell cancer cell line than finite cell lines 13 . Emerging evidence suggests FAM196B may participate in cancer development.…”
Section: Introductionmentioning
confidence: 89%